Thermal Performance Analysis of Dry Unit of Hybrid Closed Cooling Tower - Ilnur Madyshev; Vitaly Kharkov; Marsel Vakhitov; Maxim Kuznetsov (International Journal of Technology)
Effective cooling technology is essential for ensuring the sustainable development of industrial enterprises. Therefore, this study aimed to propose a hybrid closed cooling tower (CCT) with a fill unit composed of a finned pipe coil and inclined corrugated plates (ICP). A mathematical model of the hot water cooling process in the proposed cooler, operating in dry mode was developed using the number of heat transfer units (NTU). The model was validated with experimental data across different mass flow rates of process water, cooling air, and initial temperature conditions. The results showed that the finned surface of the coil pipes enhanced the heat flow rate by 2.63–3.22 times, depending on the Reynolds number by air, and improved the efficiency of heat transfer by 2.34 times.